Phenanthrenes isolated from diocorea batatas Decne peel with anti-platelet aggregation activity via direct factor Xa inhibitory activity. (October 2020) - Jeong, So Yeon; Lee, Mijeong; Lim, Ji Sun; Park, Eui Kyun; Baek, Moon-Chang; Kim, Jong-Sang; Hahn, Dongyup; Bae, Jong-Sup
Graphical abstract: Highlights: Small molecules 1 –2 from Dioscorea batatas Decne peel were isolated and they prolonged coagulation time. Compounds 1 –2 inhibited the activities and productions of FXa. Compounds 1 –2 inhibited the platelet aggregation. Compounds 1 –2 showed enhanced antithrombotic effects in vivo . Abstract: Phenanthrene is a class of phenolic metabolites present in Dioscorea batatas which has bioactivities such as antifungal, anti-inflammatory and antioxidative activities. Two phenanthrenes isolated from D. batatas Decne peel, exhibited inhibition against factor Xa and platelet aggregation. They were evaluated for their anti-FXa and anti-platelet aggregation properties by monitoring clotting time, platelet aggregation, FXa activity, and thrombus formation. They exhibited inhibition of the catalysis of FXa and inhibition of adenosine diphosphate- and U46619- induced platelet aggregation. They also inhibited phosphorylation of myristoylated alanine-rich C kinase substrate induced by ADP- and U46619 and the expression of P-selectin, while activating GP IIb/IIIa 1 in platelets. Improved production of nitric oxide and inhibition of endothelin-1 oversecretion were observed. In vivo studies demonstrated the enhanced antithrombotic effects and elicited anticoagulant effects of the compounds. Their anti-thrombotic efficacy were equivalent to rivaroxaban.